La méthode de Monte-Carlo appliquée à des problèmes d’assurance - Roy, Yves (Assurances, 1981)
On the 13th and 14th of May 1980, a seminar was held on insurance at l'Université Laval. In his paper, professor Yves Roy studied the Monte-Carlo method applied to certain insurance problems. We have pleasure in presenting it to our readers. A.